Keterampilan Variasi Mengajar Guru Di Kelas IV Sekolah Dasar Nanga Dangkan Tahun Pelajaran 2022/2023 - Wedyawati, Nelly; Bony Fransiska; Lusila Parida (LPPM Press, 2024)
This research is motivated by the findings of some problems that are often experienced by students when in class, namely experiencing boredom and boredom caused by the monotonous teaching and learning process. The research aims to determine the teacher's teaching variation skills in grade IV of Nanga Dangkan 01 Public Elementary School in the 2022/2023 academic year. This study used a qualitative approach and descriptive method; the research subjects were teachers and fourth-grade students, the research object was teaching variation skills, and the data collection techniques used were observation, direct communication, and documentation studies. Data collection tools used include observation sheets, interview sheets, and documentation. Data analysis techniques using data collection, data reduction, data presentation, and data verification. The research results obtained: 1) Teachers are skilled in applying variations in teaching styles. 2) The teacher has applied visual and kinesthetic learning media but needs to be more skilled in applying audio media. 3) The teacher has applied all aspects of variations in interaction patterns in a balanced way. 4) supporting factors due to the teacher's knowledge and understanding in creating a pleasant classroom atmosphere and the inhibiting factors experienced by the teacher, namely the availability of minimal facilities, which makes the teacher often not use learning media and the teacher's lack of creativity in creating learning media. The teaching variation skills of grade IV Elementary School teachers are seen as skilled and have been seen in applying teacher teaching variations.